STRATEGI PENGELOLAAN WISATA CANDI MUARA TAKUS BERWAWASAN LINGKUNGAN DI KAWASAN AGROPOLITAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Rahmola, Williandrie Amigo (Jurnal Kajian Lingkungan, 2014)
Research concerning Strategy Of Muara Takus Temple Management In Environmental Concept At Agropolitan Area In XIII Koto Kampar District Kampar Regency has done in December 2012 till May 2013. This research use survey method. Sample in this research use sample purposive approach. Qualitative data use observation and interview. Quantatif data use quesioner. Muara Takus Temple have some potency to develop and to get the maximum result. Some potency is Potency of area physical Muara Takus Temple, Potency of natural resources area, Potency of area facilities and basic facilities Muara Takus Temple, Potency of Sociology society around the area, Potency of development Muara Takus Temple as Pilgrimage People of Budha tourism. Problems and issues in management in Muara Takus Temple area environment is Lack facilities and basic facilities support of tourism, Lack of promotion tourism Muara Takus Temple, Lack of sinergy between stakeholders policy management Muara Takus Temple, Society Support not yet optimal, Lower visit tourism. Muara Takus Temple Existing located in quadran III. Tourism management use defensive strategy. Some strategy who recommended in Muara Takus Temple Management With Environmental Concept is Build of infrastructure, facilities and basic facilities Strategy, Promotion of Tourism Strategy, Build Tourist Information Centre Strategy, make economics of local society Strategy, make the quality of life cultural local society strategy, Map Of tourism Explore strategy. Some Factors influencing applying of strategy management of Muara Takus Temple is Human Resource with quality and with tourism concept, available budget from APBN, APBD I and of APBD II still not yet optimal, There is no coordination between stakeholders to manage Muara Takus Temple and lack of society participant and lack of Tuition from stakeholders.